Simplify (9×7)^2x / (7×9)^2y: Comparing Exponential Expressions

Question

Insert the corresponding expression:

(9×7)2x(7×9)2y= \frac{\left(9\times7\right)^{2x}}{\left(7\times9\right)^{2y}}=

Video Solution

Step-by-Step Solution

To solve the equation, you're required to simplify the expression (9×7)2x(7×9)2y \frac{\left(9\times7\right)^{2x}}{\left(7\times9\right)^{2y}} . This expression contains powers of quotients, and you can apply the properties of exponents to simplify it.

Let's go through the solution step by step:

  • Both the numerator and the denominator are raised to some powers. Notice that the base of both the numerator and the denominator is (9×7) (9 \times 7) , since 9×7=63 9 \times 7 = 63 and 7×9=63 7 \times 9 = 63 .
  • Therefore, you can rewrite the expression as (63)2x(63)2y \frac{(63)^{2x}}{(63)^{2y}} .
  • According to the property of exponents, aman=amn \frac{a^m}{a^n} = a^{m-n} , where a a is a non-zero number. Apply this rule:
  • (63)2x(63)2y=(63)2x2y \frac{(63)^{2x}}{(63)^{2y}} = (63)^{2x-2y}

With the simplification completed, you get (63)2x2y \left(63\right)^{2x-2y} .

Finally, substitute back 63 63 for 9×7 9 \times 7 , and you can express the result as (9×7)2x2y \left(9 \times 7\right)^{2x-2y} .

The solution to the question is: (9×7)2x2y \left(9\times7\right)^{2x-2y} .

Answer

(9×7)2x2y \left(9\times7\right)^{2x-2y}